As imagens amadoras de Virginia Tech em três cenas contemporâneas - Malinowski, Gabriel Gesualdi (2010)
This work aims to investigate, among the practices and representations that involve the amateur images, certain subjetive, social and media settings. For the analysis of some of these conformations, we rely on "three scenes" of the Virginia Tech massacre, which occurred in April 2007. In the first one, the student-gunman Cho Seung-hui produces and sends a Multimedia Manifesto to the television network NBC. In the second one, another student from the same university produces a video, sends it to CNN. In this video, we hear the shots of Cho. In the third scene, the first and the second videos are seen by spectators around the world. Between the modes of use, production and consumption of these images, we investigate some issues, such as perception, aesthetics, identity, work and surveillance in times of Web 2.0.